Developing English Writing Materials Using Genre Based Approach: A Case for Students of English Media Studies - Asih Rosnaningsih; Dayu Retno Puspita (English Department - University of Sultan Ageng Tirtayasa, 2020)
Teaching materials play a very important role in the learning process. A good teaching material is a collection of material contents that can facilitate teacher and students in completing the learning steps and can achieve the learning objectives appropriately. However, not all teachers provide teaching materials in accordance with the courses being taught and this makes it difficult for students to equate the perception of the material from the level of depth and the scope of the material to be learnt. This is the background of researcher to conduct this research. The purpose of this study is to develop teaching materials for writing skills in English Language Studies Media Studies for Communication Studies Students Based on Genre Based Approach. The research method being used is Research and Development (R&D). The samples are students from English of Media Studies. The result of this study produced an English writing material consisting of six topics developed by adopting Genre Based Approach in learning situation. It is hoped that teachers can use and promote this approach in teaching students writing to get maximum writing results.Key words: Teaching materials, writing skills, Genre Based Approach